ANALISIS PENGARUH KEBANGKRUTAN, AUDITOR SPESIALISASI INDUSTRI DAN CORPORATE GOVERNANCE TERHADAP FRAUDULENT FINANCIAL REPORTING - Lamoza Ressidnarry Lamoza Ressidnarry; Julianti Sjarief (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2021)
Fraudulent financial reporting often occurs in company management. Management who has a cooperation contract with the principal, there are often differences in interests between management and shareholders. The difference in interests makes it possible for management to commit fraud. Therefore, the factors that cause fraudulent financial reporting need to be known. This study aims to examine the effect of bankruptcy, auditors specializing in industry and corporate governance (consisting of managerial ownership, number of audit committee meetings and composition of independent commissioners). The population of this research is manufacturing companies in the consumer goods industry which are listed on the Indonesia Stock Exchange 2015-2018. Based on the purposive sampling method in the sample selection process, 38 companies were obtained as samples. Hypothesis testing is carried out by logistic regression analysis using the SPSS version 21 program. The results of this study are bankruptcy, managerial ownership and the composition of independent commissioners have an effect on fraudulent financial reporting. Meanwhile, auditors specializing in industry and the number of audit committee meetings have no effect on fraudulent financial reporting.